Kontruksi dan Deskontruksi Hukum Talak dan Kompilasi Hukum Islam: Studi Kritis atas Praktik Yudisial di Pengadilan Agama - Mukhammad Afrizal Sofiyan; Humaidi Kaha (Posita: Jurnal Hukum Keluarga Islam, 2025)
This study aims to critically examine the construction and deconstruction of divorce law (talak) within the Compilation of Islamic Law (KHI) and its judicial application in Religious Courts. As a source of positive law in Islamic judicial practice, KHI largely reflects the classical fiqh paradigm, which grants unilateral divorce rights to husbands. However, in practice, several judges have begun to reinterpret and deconstruct these norms to achieve substantive justice, especially for women. This research employs a normative-juridical and sociological approach, using data collected through document studies and in-depth interviews with judges and legal practitioners. The findings reveal a tension between the normative provisions of KHI and the social realities encountered in courtrooms. Judges tend to adopt a progressive, justice-oriented approach in divorce rulings, despite the constraints imposed by a conservative legal framework. These findings highlight the urgent need to reformulate divorce law in the KHI to better align with contemporary values of justice and gender equality.